The Poleward Transport of Heat by the Atmosphere - Camerlengo, Alejandro Livio; Saadon, Mohd Nasir (Universiti Putra Malaysia Press, 1998)
A warm low pressure and a cold high pressure imply the contribution of potential energy to kinetic energy. In the tropics, this represents the typical situation of the Hadley cell, also known as a direct cell. On the other hand, a cold low pressure and a warm high pressure indicate the contribution of the mean kinetic energy to the mean potential energy, which represents the typical process of the Ferell cell (also referred to as an indirect cell). This paper examines the poleward heat transport of the atmosphere. It is noted that eddies play the primary role in poleward heat transport. Furthermore, this is the way the atmosphere counterbalances the deficit of radiation at polar latitudes.